Examining pecking order versus trade-off theories of capital structure: New evidence from Japanese firms - Salim, Ruhul; Jarallah, S.; Saleh, A. (John Wiley and Sons, 2018)
This study empirically tests the traditional trade‐off model against the pecking order model of capital structure using data from the Japanese listed companies on the Tokyo Stock Exchange. A pooled sample of 1,362 publicly listed nonfinancial companies from 1991 to 2015 is used to establish the relationship between leverage and its determinants by using the generalized methods of moments econometric framework. The results show that the financing pattern of Japanese firms is consistent with the basic pecking order model, which predicts external debt financing driven by the internal financial deficit.